Proceedings of the 17th International Conference on Hybrid Systems: Computation and Control 2014
DOI: 10.1145/2562059.2562126
|View full text |Cite
|
Sign up to set email alerts
|

Proofs from simulations and modular annotations

Abstract: We present a modular technique for simulation-based bounded verification for nonlinear dynamical systems. We introduce the notion of input-to-state discrepancy of each subsystem Ai in a larger nonlinear dynamical system A which bounds the distance between two (possibly diverging) trajectories of Ai in terms of their initial states and inputs. Using the IS discrepancy functions, we construct a low dimensional deterministic dynamical system M (δ). For any two trajectories of A starting δ distance apart, we show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 23 publications
0
31
0
Order By: Relevance
“…For discrete or discretized systems, translations to formal models like extended input/output automata have been developed [19]. Some recent simulation-based verification, testing, and falsification approaches in hybrid systems and CPS like those in S-TaLiRo, Breach, and C2E2 can be viewed as forms of dynamic analysis (potentially with additional annotations and proof steps) [26,28,29,[39][40][41]. Additionally, there are alternative methods for finding specifications for SLSF models [29,39].…”
Section: Related Workmentioning
confidence: 99%
“…For discrete or discretized systems, translations to formal models like extended input/output automata have been developed [19]. Some recent simulation-based verification, testing, and falsification approaches in hybrid systems and CPS like those in S-TaLiRo, Breach, and C2E2 can be viewed as forms of dynamic analysis (potentially with additional annotations and proof steps) [26,28,29,[39][40][41]. Additionally, there are alternative methods for finding specifications for SLSF models [29,39].…”
Section: Related Workmentioning
confidence: 99%
“…First of all, we will use the definition of Input-to-State (IS) discrepancy function [27], which enables us to use annotations for individual modules in a dynamical system to then check invariants of the composed system. The IS discrepancy function for a location of A (or for a dynamical system) bounds the distance between two trajectories in location from different initial states, as a function of time and the inputs they receive.…”
Section: Is Discrepancy and Approximationsmentioning
confidence: 99%
“…The result is generalized to dynamical systems with N modules connected in general network topologies [27], where the IS approximation is (N + 1)-dimensional.…”
Section: Is Discrepancy and Approximationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, it is important that the over-approximation can be made more precise so that false positives can be eliminated. To turn this idea into an algorithm, we introduced the notion of discrepancy which (a) upper bounds the distance between two neighboring behaviors and (b) the bound converges to zero as the parameter choices for the two behaviors get closer and closer [6], [8]. It has been shown that, for an expressive class of models, indeed one can find discrepancy functions that meet these criteria [7].…”
Section: Introductionmentioning
confidence: 99%